An international consortium proposal of uniform response criteria for myelodysplastic/myeloproliferative neoplasms (MDS/MPN) in adults - Savona, Michael R.; Malcovati, Luca; Komrokji, Rami; Tiu, Ramon V.; Mughal, Tariq I.; Orazi, Attilio; Kiladjian, Jean-Jacques; Padron, Eric; Solary, Eric; Tibes, Raoul; Itzykson, Raphael; Cazzola, Mario; et al. (Blood, 2015)
Myelodysplastic syndromes (MDS) and myeloproliferative neoplasms (MPN) are hematologically diverse stem cell malignancies sharing phenotypic features of both myelodysplastic syndromes and myeloproliferative neoplasms. There are currently no standard treatment recommendations for most adult patients with MDS/MPN. To optimize efforts to improve the management and disease outcomes, it is essential to identify meaningful clinical and biologic end points and standardized response criteria for clinical trials. The dual dysplastic and proliferative features in these stem cell malignancies define their uniqueness and challenges. We propose response assessment guidelines to harmonize future clinical trials with the principal objective of establishing suitable treatment algorithms. An international panel comprising laboratory and clinical experts in MDS/MPN was established involving 3 independent academic MDS/MPN workshops (March 2013, December 2013, and June 2014). These recommendations are the result of this collaborative project sponsored by the MDS Foundation.